2006
DOI: 10.1038/sj.onc.1209981
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooxygenase inhibitors modulate the p53/HDM2 pathway and enhance chemotherapy-induced apoptosis in neuroblastoma

Abstract: Cyclooxygenase-2 (COX-2) is upregulated in many tumors including neuroblastoma, and its overexpression has been implicated in resistance to p53-dependent apoptosis. Although p53 is rarely mutated in neuroblastoma, the p53 protein is rendered inactive via several mechanisms including sequestration in the cytoplasm. Here, we show that COX inhibitors inhibit the growth of neuroblastoma and when combined with low doses of chemotherapy, exert synergistic effects on neuroblastoma cells. Following COX inhibitor treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 46 publications
1
37
0
1
Order By: Relevance
“…We have previously demonstrated that selective and non-selective COX inhibitors induce cell death in neuroblastoma, in part due to p53-dependent apoptosis (Lau et al, 2007). The selective COX-2 inhibitor celecoxib also suppressed the proliferation of p53-mutant neuroblastoma cells (SK-N-BE2, SK-N-FI and SK-N-AS) in vitro ( Figure 2a) and inhibited the growth of SK-N-BE2 xenografts (data not shown).…”
Section: Cox Inhibitors Suppress Cell Growth In Neuroblastomamentioning
confidence: 73%
See 2 more Smart Citations
“…We have previously demonstrated that selective and non-selective COX inhibitors induce cell death in neuroblastoma, in part due to p53-dependent apoptosis (Lau et al, 2007). The selective COX-2 inhibitor celecoxib also suppressed the proliferation of p53-mutant neuroblastoma cells (SK-N-BE2, SK-N-FI and SK-N-AS) in vitro ( Figure 2a) and inhibited the growth of SK-N-BE2 xenografts (data not shown).…”
Section: Cox Inhibitors Suppress Cell Growth In Neuroblastomamentioning
confidence: 73%
“…In addition, COX inhibitors have also been shown to target COX-2 independent signaling pathways (reviewed in Kashfi and Rigas (2005) and Grosch et al (2006)). We have shown that COX inhibitors modulate the p53/HDM2 pathway, resulting in increased p53 stability and nuclear accumulation (Lau et al, 2007). We observed that neuroblastoma cells harboring mutant-p53 were also sensitive to COX inhibitors, prompting us to ask whether p73 was involved in the potentiation of chemosensitivity by COX inhibitors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with this, Cox-2 inhibitors enhanced chemosensitivity by downregulating HDM2 thereby augmenting p53 stability. 150 Secondly, Cox-2 was shown to physically interact with p53 both in vitro and in vivo suppressing not only basal, but also activation-induced transcriptional activity of p53, an effect that was mimicked by the addition of prostaglandin and abrogated by NS-398. 150 Such a negative feedback mechanism might be especially important during inflammatory responses that also result in DNA damage and that require the pro-apoptotic capabilities of p53 to be kept tightly in check.…”
Section: P53 and Mitogen-activated Protein Kinasesmentioning
confidence: 99%
“…150 Secondly, Cox-2 was shown to physically interact with p53 both in vitro and in vivo suppressing not only basal, but also activation-induced transcriptional activity of p53, an effect that was mimicked by the addition of prostaglandin and abrogated by NS-398. 150 Such a negative feedback mechanism might be especially important during inflammatory responses that also result in DNA damage and that require the pro-apoptotic capabilities of p53 to be kept tightly in check. 148 Although it remains to be elucidated whether p53 induces HB-EGF expression (and subsequently Akt and Cox-2 activation) in a direct or indirect manner, with the induction of this and the DDR1 pathway, p53 entails powerful antiapoptotic mechanisms that appear to be crucial determinants for the maintenance of the delicate balance between life and death in response to DNA damage.…”
Section: P53 and Mitogen-activated Protein Kinasesmentioning
confidence: 99%